2010
DOI: 10.1038/cr.2010.108
|View full text |Cite
|
Sign up to set email alerts
|

Dishevelled interacts with p65 and acts as a repressor of NF-κB-mediated transcription

Abstract: Dishevelled (Dvl) is a highly conserved protein family that plays an important role in mediating Wnt signaling from membrane to cytoplasm. Recently we reported that Dvl also functions in the nucleus by stabilizing the β-catenin/TCFs transcriptional complex. Here we describe that Dvl may function as a repressor of NF-κB. Our data show that Dvl directly binds to p65 and their interaction occurs in the nucleus. Dvl expression inhibits p65-mediated or TNF-α-stimulated activation of the NF-κB dependent reporter. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
(39 reference statements)
3
13
0
Order By: Relevance
“…The results showed that overexpression of Dvl2 inhibited TNF-α-induced nuclear translocation of P65 (Figure 6A). Deng N et al reported that Dvl can interact with P65 in HEK293T cells [26], and our immunoprecipitation (IP) analysis also showed interaction between Dvl2 and P65 in RA-FLSs (Figure 6B). A subsequent chromosome immunoprecipitation (ChIP) assay revealed that Dvl2 inhibited TNF-α-induced binding of P65 to the promoters of anti-apoptotic and inflammatory genes (Figure 6C, 6D).…”
Section: Resultssupporting
confidence: 71%
“…The results showed that overexpression of Dvl2 inhibited TNF-α-induced nuclear translocation of P65 (Figure 6A). Deng N et al reported that Dvl can interact with P65 in HEK293T cells [26], and our immunoprecipitation (IP) analysis also showed interaction between Dvl2 and P65 in RA-FLSs (Figure 6B). A subsequent chromosome immunoprecipitation (ChIP) assay revealed that Dvl2 inhibited TNF-α-induced binding of P65 to the promoters of anti-apoptotic and inflammatory genes (Figure 6C, 6D).…”
Section: Resultssupporting
confidence: 71%
“…On the other hand, recent findings indicated that Dvl also exists in the nucleus (9,14,41) and participates in ␤-catenin-T-cell factor (TCF) transcriptional complex formation by interacting with ␤-catenin and c-Jun, thus promoting canonical Wnt signaling (9). In addition, Dvl was also reported to interact with p65 in the nucleus to inhibit p65-mediated transcription (8).…”
mentioning
confidence: 99%
“…Free p65 subsequently translocates into the nucleus where it functions as a transcription factor in regulating its target genes . Prior study had suggested that Dvl interacted with p65 in the nucleus and inhibited NF‐κB‐mediated transcription . In this study, we have demonstrated that Dvl‐3 transfection promoted phosphorylation of IκB‐α and facilitated nuclear translocation of p65, suggesting p65 may be activated by Dvl‐3 induced phosphorylation of IκB‐α.…”
Section: Discussionmentioning
confidence: 49%